RESPON SORGUM (Sorghum bicolor) TERHADAP PENGURANGAN DOSIS PUPUK ANJURAN - Retno Dwi Andayani (Universitas Tribhuwana Tunggadewi, 2020)
The requirements for rice as the staple food in Indonesia tends to increase every year along with the increase in population. As anticipation, an alternative that can be taken is to increase the productivity of carbohydrate-producing crops as the main non-rice food source on dry land. Sorghum is a versatile plant that can be used as a source of food, animal feed, and industrial raw materials. The purpose of this study was to determine the production of 3 varieties of sorghum to reduce the dose of NPK fertilizer. The research was conducted in Sumber Agung Village, Plosoklaten, Kediri Regency in May-August 2020. The research used a factorial randomized block design with the first factor being 3 varieties of sorghum, namely Kawali, Numbu, and Suri 4, the second factor was the dose of NPK fertilizer, which was 100%, 75 %, 50%, 25%, and 0%. The results showed an interaction between sorghum varieties and fertilization doses. Kawali variety only produces maximum if fertilization is 100%, Numbu variety still produces maximum at 50% fertilization and Suri 4 variety can still produce maximum at 25% fertilization.